Intellectual structure of strategic management research in the hospitality management field: A co-citation analysis. (April 2019) - Köseoglu, Mehmet Ali; Okumus, Fevzi; Dogan, Ismail Cagri; Law, Rob
Highlights: This study investigates the intellectual structure of strategic management research in the hospitality field. Data were collected from related articles published during the period 1971 to 2016. The resource-based view is a dominant approach in the field although the positioning school was dominant during the early stages of the field. The structural equation model and data envelopment analysis are dominant quantitative methods in the field. Ideas from marketing are one of the roots of hospitality SM research. Abstract: This study investigates the intellectual structure of strategic management (SM) research in the hospitality industry through co-citation analysis. This study analyzes the evolution of SM research from related SM articles inclusively published in hospitality- and tourism-focused journals as well as business- and management-focused journals from 1971 to 2016. This study is the first to map the intellectual structure of SM research in the hospitality industry to analyze the changes in the influence of the most significant studies, journals, and disciplines/fields as well as the relationships among the subfields on SM research in the hospitality industry. This study suggests that marketing is a dominant subfield in SM research within the hospitality industry. In addition, the resource-based view is a dominant approach in the field, although the positioning school was dominant during the field's early stages.